Good Practice Note for Energy Sector Adaptation - World Bank (Washington, DC : World Bank, 2022)
Climate change poses direct risks to power sector investments, as the components of this sector are highly sensitive to environmental variables such water availability, extreme weather, and flooding. With this in mind, it is imperative to account for and address these changing conditions during development and design for WB-financed power sector infrastructure. The World Bank has made a commitment to mainstream climate change into its operations and scaling up action for climate adaptation. This good practice note aims to assist World Bank task teams in incorporating climate adaptation and resilience into power sector projects for client countries.